Emergency amputation necessitated within 24 hours by a human bite: a case report. Issue 5 (May 2021) - Zhu, Guozheng; Zeng, Canjun; Yuan, Song; Li, Runguang
We herein review and analyze the diagnosis, treatment, and outcome of a severe infection caused by a human bite. A 68-year-old man was bitten on the forearm by a 3-year-old child. Rapid progression of infection, severe local and systemic poisoning, and diverse clinical manifestations were observed at presentation. Based on the medical history, physical signs, imaging examinations (X-ray films, color Doppler ultrasound, and computed tomography), laboratory examinations, and multidisciplinary consultation, the patient was diagnosed with gas gangrene or gas gangrene-like changes. Twenty-four hours after the injury, an emergency amputation was performed (open amputation with wound closure after 1 week). After the operation, the patient was sent to the intensive care unit for isolation and further anti-infection and anti-shock treatments. His condition gradually improved after treatment and he was discharged without further complications. Bacteriological and pathological examinations indicated Aeromonas hydrophila infection leading to extensive necrotizing fasciitis of the limb and severe systemic poisoning. In addition, pre-existing myelodysplastic syndrome progressing to acute myeloid leukemia was identified as a possible predisposing factor. Human bites can cause serious infections requiring timely treatment, particularly in patients with predisposing comorbidities.